Capitalizing on Informality: Varieties of Actually Existing Informal Economies in Africa. Issue 1 (18th August 2017) - Meagher, Kate
Abstract : This paper explores the potential of the informal economy to contribute to economic development in contemporary Africa. New models of market development variously referred to as inclusive business or inclusive capitalism call for greater inclusion of informal economies in development processes, raising questions about the nature of African informality and its actual transformative potential. This paper takes up the task of deciphering the institutional character and potential contribution of the informal economy to economic development in various parts of Africa. Adopting a comparative perspective that explores the differences among informal economies in different regions of the continent, this paper examines how distinctive pre‐colonial, colonial and post‐colonial histories have shaped distinctive paths of informal economic organization in East, West and Southern Africa. This has laid a foundation for varied responses to economic reform and globalization, triggering differential responses in terms of the size, entrepreneurial capacity, and labour composition within African informal economies. The paper will conclude with reflection on the varied potential of African informal economies to contribute to economic transformation, focusing on the institutional resources and political‐economic tensions that shape distinctive institutional trajectories of economic resilience, vulnerability and dysfunction in various parts of the continent.